Dual-targeting CAR T cells for B-cell acute lymphoblastic leukemia and B-cell non-Hodgkin lymphoma - Gustavo de Oliveira Canedo; Claire Roddie; Persis J. Amrolia (Blood Advances)
Abstract: Relapse after CD19-directed chimeric antigen receptor (CAR) T-cell therapy remains a major challenge in B-cell acute lymphoblastic leukemia (ALL) and B-cell non-Hodgkin lymphoma (B-NHL). One of the main strategies to avoid CD19-negative relapse has been the development of dual CAR T cells targeting CD19 and an additional target, such as CD22 or CD20. Different methods have been used to achieve this, including coadministration of 2 products targeting 1 single antigen, cotransduction of autologous T cells, use of a bicistronic vector, or the development of bivalent CARs. Phase 1 and 2 trials across all manufacturing strategies have shown this to be a safe approach with equivalent remission rates and initial product expansion. CAR T-cell persistence remains a significant issue, with the majority of relapses being antigen-positive after CAR T-cell infusion. Further, despite adding a second antigen, antigen-negative relapses have not yet been eliminated. This review summarizes the state of the art with dual-targeting CAR T cells for B-cell ALL and B-NHL, the challenges encountered, and possible next steps to overcome them.